Aspects of mobile phone use and behavioural intentions for learning in rural South African schools - Merwe, Mc Donald Van Der; Bonyongwa, Tariro (Journal of Education and e-Learning Research, 2024)
This paper focuses on a study conducted in two historically disadvantaged schools (deep-rural and semi-urban) in South Africa where the rising access to mobile technology implies that the long-standing promise of mobile learning is becoming accessible despite the lack of recent research. This research aims to investigate the relationship between the type of school and various aspects of mobile phone use as well as differences in behavioural intention constructs to use mobile phones for learning. After a literature review, several hypotheses were developed. Using non-probability sampling techniques and the survey method, data was obtained from 128 participants, 79 from the deep-rural school and 49 from the semi-urban school. The semi-urban school exhibited slightly higher percentages in all aspects of cell phone use. Outside of mobile phone ownership and Internet access, all associations were significant. Significant differences were reported in favour of the semi-urban school for all constructs regarding the behavioural intention to use mobile phones for learning. However, the future of m-learning appears to be more promising than reported in earlier research by reporting positive behaviour from students in both schools. Critical stakeholders in education should take note and move from the goals of improving broad access to explicit objectives to implement m-learning in rural schools.